The effect of local dents on the residual ultimate strength of 2024-T3 aluminum alloy plate used in aircraft under axial tension tests. (February 2015) - Li, Zhigang; Zhang, Dingni; Peng, Chunlei; Ma, Chunsheng; Zhang, Jinhuan; Hu, Zhongmin; Zhang, Jiazhen; Zhao, Yanan
Highlights: We conducted drop-weight impact tests on 2024-T3 aluminum alloy to generate dents. Effect of dents on tension strength of the aluminum alloy plate was investigated. Dents can significantly reduce the ultimate tension strength of the aluminum alloy. Mathematical formulas between ultimate strength and the dent depth were obtained. Abstract: Local dent is a typical damage of aircraft, however, very few studies have investigated the effect of dents on the residual ultimate strength of the aluminum plate under different loading conditions, especially under tensions. In this study, drop-weight impact tests were conducted on the 2024-T3 aluminum alloy plate to generate 5 types of dents, and then tension tests were performed on the dented specimens to investigate the effects of the dents on the residual ultimate strength. Results show that the residual ultimate strength and the fracture displacement of the plate are significantly affected by the local dents. With increase in the depths of spherical, V-shape, and elliptical dents, the ultimate strengths decrease in quadratic trend. Whereas, for the conical and U-shape dent, linear relationships were observed between dent depth and the ultimate strength. The mathematical formulas between the ultimate strength reduction rate and the dent depth reduction factors were derived through regression analysis on the experimental results.